The Cushion Region and Dayside Magnetodisc Structure at Saturn. Issue 6 (25th March 2021) - Staniland, N. R.; Dougherty, M. K.; Masters, A.; Achilleos, N.
Abstract: A sustained quasi‐dipolar magnetic field between the current sheet outer edge and the magnetopause, known as a cushion region, has previously been observed at Jupiter, but not yet at Saturn. Using the complete Cassini magnetometer data, the first evidence of a cushion region forming at Saturn is shown. Only five examples of a sustained cushion are found, revealing this phenomenon to be rare. Four of the cushion regions are identified at dusk and one pre‐noon. It is suggested that greater heating of plasma post‐noon coupled with the expansion of the field through the afternoon sector makes the disc more unstable in this region. These results highlight a key difference between the Saturn and Jupiter systems. Plain Language Summary: The presence of the moons Enceladus and Io provide an internal source of plasma to the magnetospheres of Saturn and Jupiter, respectively. This, coupled with their rapid rotation rates (approximately 10 h), radially stretches the magnetic field at the equator away from a dipole configuration to what is known as a magnetodisc. However, this structure can break down at large distances where the magnetic field can no longer contain the plasma and the field becomes dipolar, known as a "cushion region." This has previously been observed at Jupiter, but not at Saturn. We present the first evidence of a cushion region forming at Saturn. We find only five examples, showing it to be rare, with four at local time dusk and one pre‐noon. The dusk cushion we have observed could be due to asymmetric heating of plasma in the Saturn system, as well as the changing magnetic field configuration as the plasma moves through noon into a less compressed region, resulting in disc instabilities. These results show a key difference between the Saturn and Jupiter system, where at Jupiter the cushion is a result of large‐scale reconnection in the tail and return flow. Key Points: The first example of a cushion region at Saturn is identified Only five examples of a cushion are identified, showing this phenomenon to be rare, with four at dusk and one at dawn The dusk cushion could form due to the greater heating of plasma and the expansion of the field in the afternoon sector